Potrzeba rozmowy o zdarzeniu traumatycznym a poziom symptomów PTSD - Dudek, Bohdan; Szymczak, Wiesław (Acta Universitatis Lodziensis. Folia Psychologica, 2010)
There were many studies on treatment and prophylaxis of PTSD. It was assumed that a need of talking about of the traumatic event has been a factor moderating relationship between exposure to traumatic event and PTSD symptoms development. Aim of the study was to test this assumption. The study was conducted on police officers according longitudinal procedure, it means that the study was performed in two stages with one year break. It was a possibility to make an analysis of obtained results as if it were two studies; cross-sectional and longitudinal ones. Each analysis let us draw opposing conclusions. Need of talking about traumatic event appeared to be a resistance factor in former one and a sensibilizing factor in letter one.